Analyzing Pattern of Mutation in mtDNA Using Markov Chain - Lira Adiyani; Sutawanir Darwis; Achmad Saifuddin Noer (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2008)
Mutation in mtDNA becomes an interesting topic that needed to discuss. If someone has a mutationin his mtDNA, then it might be affect his health. Those effects could be some diseases or anothervariation that gives different characteristics. In study of mutation, there are two such things becomethe main problems: (1) does mutation occur dependently? and (2) what is the pattern? From theresearch (by 9 degrees of freedom χ2), DNA sequence shows a positional dependence. In addition, wecan also see a positional dependence in mtDNA sequence clearly (position i-1, i, i+1 are dependentwith i define as mutation) by sign test, which means, it is possibly that there is a pattern of mutation.This paper uses Markov chain to quantify the pattern and as results all bases will mutate if positioni+1 is C or cytosine (±40%). Moreover, A, C, and G will mutate (become T) if position i-1 is A oradenine (54.5%).